The empirics of long-term Mexican government bond yields - Tanweer Akram; Syed Helal Uddin (Levy Economics Institute of Bard College, 2021)
This paper presents empirical models of Mexican government bond (MGB) yields based on monthly macroeconomic data. The current short-term interest rate has a decisive influence on MGB yields, after controlling for inflation and growth in industrial production. John Maynard Keynes claimed that government bond yields move in lockstep with the short-term interest rate. The models presented in the paper show that Keynes's claim holds for MGB yields. This has important policy implications for Mexico. The empirical findings of the paper are also relevant for ongoing debates in macroeconomics.
Keywords: E43; E50; E58; E60; G10; G12; 330; Mexican Government Bonds; Long-Term Interest Rate; Short-Term InterestRate; Monetary Policy; Banco de México (BdM); Banxico